Recurrent Haematuria in a Toddler: A Journey from Suspected UTI to Precocious Puberty - Nurul Husna Azmi; Najihah Abdul Razak; Mohammad Che Man (Asian Journal of Medicine & Health Sciences, 2024)
Numerous factors can contribute to the presence of blood in the urine. While the causes of gross haematuria often suggest a urological origin, it may also result from gynaecological pathology contaminating the urine. We present a case of a 2-year-2-month-old girl who presented with recurrent haematuria, her third episode in five months. Her previous two episodes were treated as urinary tract infections (UTI). One week before this most recent presentation, she had an upper respiratory tract infection, which resolved with a course of antibiotics. Although she was normotensive, she was referred to a tertiary centre for suspected post-streptococcal glomerulonephritis, based on urinalysis findings of erythrocytes 3+, trace proteinuria and presence of leukocytes. At the hospital, she was initially treated with antibiotics for probable UTI. However, persistent fresh blood staining her diaper prompted a second genital evaluation, which revealed blood seeping from the vagina. Further assessment showed signs of puberty suggesting that menstruation was contaminating the urine sample. This case report highlights the need for clinicians to consider a broad differential diagnosis when evaluating haematuria in paediatric patients and the importance of thoroughly assessing secondary sexual characteristics in young girls with haematuria to facilitate early recognition of precocious puberty.